TINGKAT KECEMASAN PRABEDAH PADA PASIEN FRAKTUR DI RUMAH SAKIT UMUM DAERAH MEURAXA BANDA ACEH - Fakhrul Rizal; Risha Simahate Bengi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2021)
Fracture is a severance of bone continuity caused by trauma due to pressure that exceeds the bone pressure resistance. The efforts to restore the structure and function of bones may require surgery. Surgery is a potential or actual threat to someone as surgery may cause anxiety symptoms and can be a difficult experience for the patient. The purpose of this study is to analyze the age, sex, level of education, history of surgery, and type of fracture with the anxiety level of patients with pre-fracture surgery at Meuraxa Regional Public Hospital, Banda Aceh. This research uses a descriptive observational analytic method with cross-sectional study design. The sample consists of 35 respondents selected by Consecutive Sampling. The samples then analyzed univariately with a frequency distribution table and bivariate. Statistical test results show that gender (P (0.286)(0.05))and level of education (P(0.404(0.05))do not contribute significantly to anxiety level, but there is significant level of anxiety from the three other variables namely age (P (0.0240.05)), history of surgery (P(0.0000.05)), type of fracture (P (0.0000.05)). From these results, an intervention to provide detailed and clear information and education to the patients about the procedure for fracture surgery can decrease the anxiety level.Keywords: Anciety, Preoperative, Fracture